Sustainability transformations agents and drivers across societies - Linnér, Björn-Ola (Cambridge University Press, 2019)
Societal transformations are needed across the globe in light of pressing environmental issues. This need to transform is increasingly acknowledged in policy, planning, academic debate, and media, whether it is to achieve decarbonization, resilience, national development plans, or sustainability objectives. This volume provides the first comprehensive comparison of how sustainability transformations are understood across societies. It contains historical analogies and concrete examples from around the world to show how societal transformations could achieve the Paris Agreement and the United Nations Sustainable Development Goals through governance, innovations, lifestyle changes, education and new narratives. It examines how societal actors in different geographical, political and cultural contexts understand the agents and drivers of societal change towards sustainability, using data from the academic literature, international news media, lay people's focus groups across five continents, and international politics. This is a valuable resource for academics and policymakers working in environmental governance and sustainability.